Pengaruh Model Pembelajaran Course Review Horay (CRH) Terhadap Hasil Belajar Siswa Pada Kompetensi Dasar Memahami Administrasi Kelas OTKP SMK Negeri 10 Surabaya - Cyntya Dwi Wahyuningtyas; Siti Sri Wulandari (Jurnal Pendidikan Administrasi Perkantoran (JPAP), 2020)
The background of this research is because there are still many student learning outcomes in administrative subjects under the KKM. That's because the teacher learning model still uses the direct learning model, many tend to speak for themselves, passive learning resources and are still teacher-centered. This study aims to determine the effect of the horay course review learning model on student learning outcomes right on basic competencies in understanding administration. This type of research design is a quasi-experimental design with nonequivalent control group design. The research subjects were class X OTKP 3 as the control class and X OTKP 4 as the experimental class. The research instrument was a pre-test and post-test learning outcome sheet. The results of this study indicate that the tcount is 2.755, Sig. (2-tailed) is 0.007 and the confidence level is 95% (Î± = 0.05) with df 70, then the table = 1.994. So it can be seen that Ha1 is accepted & Ho1 is rejected. Because t-test <0.05 is 0.007 <0.05, and t count 2.755> 1.994 tables. Significant improvement in learning outcomes in the experimental class was 26.66 or 52.72%. While the control class increased learning outcomes by 18.06 or 49.82%, and the application of the CRH learning model can make students more interactive learning. So it can be concluded that there is an effect of Course Review Horay (CRH) learning model on student learning outcomes on basic competencies in understanding the administration of Class X OTKP SMK Negeri 10 Surabaya.